2015
DOI: 10.1149/2.0181514jes
|View full text |Cite
|
Sign up to set email alerts
|

Differential Thermal Analysis of Li-Ion Cells as an Effective Probe of Liquid Electrolyte Evolution during Aging

Abstract: A technique has been developed to allow for in-situ observation of the state of the liquid electrolyte present in an electrochemical device through exploiting the nature of solid-liquid phase transitions. An apparatus was developed to perform differential thermal analysis (DTA) on complete NMC/graphite lithium-ion pouch cells. The DTA apparatus monitored the temperature of a sample cell alongside that of a thermally inert reference cell during a controlled temperature scan through the melting point of the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 15 publications
2
67
0
Order By: Relevance
“…Since transition metal dissolution has been shown to be driven by HF formation from PF 6 − , 30 it could also be that the difference in the results from this study and the Gilbert study originates from relative amounts of formed PF 5 and HF. This is also consistent with the lack of dimerization products measured in the electrolyte in this study.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Since transition metal dissolution has been shown to be driven by HF formation from PF 6 − , 30 it could also be that the difference in the results from this study and the Gilbert study originates from relative amounts of formed PF 5 and HF. This is also consistent with the lack of dimerization products measured in the electrolyte in this study.…”
Section: Resultsmentioning
confidence: 66%
“…The PTFE vial is then machine shaken in two directions for a total of 30 minutes. Some of the extract is removed and filtered with a syringe filter containing a PTFE membrane with a 0.45 μm pore size into a second PTFE vial containing additional CH 2 Cl 2 and deionized-water for LiPF 6 and HF extraction. 17 The new solution is then shaken for another 5 minutes, centrifuged for 20 minutes at 2200 RPM (800 g) to separate the organic and inorganic layers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Day et al 46 showed that depletion of LiPF 6 salt occurred during aggressive charge-discharge cycling to 4.5 V in NMC442/graphite cells at 55…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] It was generally believed that the graphite electrode could not be electrochemically lithiated in most common solvents, including ethers, esters, butyrolactones and propylene carbonate, without the sacrificial reaction of EC to form the SEI. 6 While the passivation of graphite is virtually complete during the first few cycles, the remaining EC in the electrolyte can be oxidized at high voltages, causing the performance of cells containing EC to diminish as the upper charge voltage increases above 4.4 V. 7,8 Electrolyte oxidation at the positive electrode at high potentials can lead to salt consumption 9 and gas evolution. 10 Precipitation of electrolyte oxidation by-products onto the surface of the positive and negative electrodes causes polarization and impedance growth, 11,12 which can limit cycle life.…”
mentioning
confidence: 99%